HOUSING PROVISION FOR FACTORY WORKERS - Liliany S Arifin (Dimensi: Journal of Architecture and Built Environment, 2001)
The need of factory worker housing cannot be denied during the period of industrialization. In fact, from early 18 century in Europe and at the end of 20 century in Asia, industrialization have been bringing the problem of housing for their workers, but only few attention are given by governments or companies. This study is a secondary study and at the end offers some arguments that can be used as further implication research.